2005
DOI: 10.1042/bc20040511
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative FRET imaging of leptin receptor oligomerization kinetics in single cells

Abstract: Both methods yielded similar results, indicating that (1) leptin receptors expressed in the cell membrane exist mostly as preformed LEPRa/LEPRa or LEPRb/LEPRb homo-oligomers but not as LEPRb/LEPRa hetero-oligomers; (2) the appearance of transient leptin-induced FRET in cells transfected with LEPRb/LEPRb reflects both a conformational change that leads to closer interaction in the cytosolic part and a higher FRET signal, as well as de novo homo-oligomerization; (3) in LEPRa/LEPRa, exposure to leptin does not le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 51 publications
(64 reference statements)
2
39
1
Order By: Relevance
“…The fluorescence emission was directed back out into the detection unit through a short-pass filter (l < 750 nm). The FLIM unit was composed of a streak camera (Streakscope C4334; Hamamatsu Photonics) coupled to a fast and high-sensitivity CCD camera (model C8800-53C; Hamamatsu) (Krishnan et al, 2003;Biener et al, 2005). For each nucleus, average fluorescence decay profiles were plotted and lifetimes were estimated by fitting data with biexponential function using a nonlinear least squares estimation procedure with Origin 7.5 software (OriginLab).…”
Section: Flim and Data Analysismentioning
confidence: 99%
“…The fluorescence emission was directed back out into the detection unit through a short-pass filter (l < 750 nm). The FLIM unit was composed of a streak camera (Streakscope C4334; Hamamatsu Photonics) coupled to a fast and high-sensitivity CCD camera (model C8800-53C; Hamamatsu) (Krishnan et al, 2003;Biener et al, 2005). For each nucleus, average fluorescence decay profiles were plotted and lifetimes were estimated by fitting data with biexponential function using a nonlinear least squares estimation procedure with Origin 7.5 software (OriginLab).…”
Section: Flim and Data Analysismentioning
confidence: 99%
“…Homodimerization of unstimulated leptin b receptors yields FRET efficiencies of 4.9% by the acceptor photobleaching method, the same method used in this study (Biener et al, 2005). Homodimers are expected to yield FRET signals that are half the intensity of heterodimers, resulting from the unavoidable formation of YFP-␤3/YFP-␤3 dimer and CFP-␤3/CFP-␤3 dimers that do not yield FRET signals upon acceptor photobleaching.…”
Section: Discussionmentioning
confidence: 89%
“…Earlier studies suggested ligand-independent dimerization or oligomerization of the LR ECD in solution , but recent evidence obtained by multi-angle laser light scattering (MALLS) and smallangle X-ray scattering (SAXS) experiments has now indicated that it is monomeric in the absence of leptin (Mancour et al 2012, Moharana et al 2014. On the membrane, however, the LR can assemble as preformed dimers or oligomers, as evidenced by a high basal signal in the absence of leptin in both fluorescence resonance energy transfer (FRET) and bioluminescence resonance energy transfer (BRET) between differently tagged LRs and by co-immunoprecipitation of tagged LRs (Nakashima et al 1997, White & Tartaglia 1999, Couturier & Jockers 2003, Biener et al 2005. Different isoforms of the LR can heterodimerize with each other both in the presence and absence of leptin (White & Tartaglia 1999, Bacart et al 2010.…”
Section: Disulfide Network and Glycosylation Of The Ecdmentioning
confidence: 99%
“…Different isoforms of the LR can heterodimerize with each other both in the presence and absence of leptin (White & Tartaglia 1999, Bacart et al 2010. Leptin treatment induces an increase in BRET and FRET signals, which are probably a consequence of reorganization within the pre-formed complexes and/or de novo oligomerization (Couturier & Jockers 2003, Biener et al 2005.…”
Section: Disulfide Network and Glycosylation Of The Ecdmentioning
confidence: 99%